Novi oltarni in reliefni kamni iz Petovione - Tušek, Ivan (Arheološki vestnik, 1993)
In the article the author publishes some new inscriptions - reliefs from Ptuj: an altar dedicated to Juppiter from the end of the Is1 or the beginning of the 2nd Centuries, which was erected by a romanised Celtic native with the so far unrecorded gentile name of Geusius. Two marble relief slabs with representations of the Nutrices: one represents four female figures, the other, which was assumed to have been lost and bears the dedication AIJ 326, has two. Two acroteria from the lid of a sarcophagus, one of which bears a representation of the genius of summer, whilst the other bears the genius of autumn. The author mentions another relief, which bears the figures of a dog and a bear and a fragment with a relief of a horned roc deer.